Influence of interface steps on the buckle delamination of thin films. (November 2019) - Parry, G.; Hamade, S.; Durinck, J.; Coupeau, C.; Colin, J.
Highlights: Step induced buckle deviation is observed for Ni/LiF bilayer system. Finite element simulations of the buckle propagation near a step are performed. The height and inclination of the step are key parameters. Interacting buckles on a step may escape from it. Abstract: The mechanics of thin film buckle delamination has been widely studied, with the assumption of perfect (flat) interfaces. This work is reporting a study of the evolution of an initially straight-sided buckle propagating in a thin film lying on a substrate in the presence of a step at the film/substrate interface, resulting from the plastic deformation of the substrate. Assuming the interface toughness depends on the mode mixity, it has been found using finite elements calculations that depending on the step orientation and height, the initially straight propagation of the buckle can be perturbed so that the buckle eventually propagates along the step. The critical parameters (orientation and height) of the step have been then determined, which characterizes the transition from a straight propagation perpendicular to the compression axis to a propagation along the inclined step. A "behavior" diagram has been finally presented for the buckle, where the propagation, either perpendicularly to the step or along it have been displayed versus the step height and orientation.